Studying Brown Adipose Tissue in a Human in vitro Context - Samuelson, Isabella; Vidal-Puig, Antonio (Frontiers in Endocrinology, 2020)
New treatments for obesity and associated metabolic disease are increasingly warranted with the growth of the obesity pandemic. Brown adipose tissue (BAT) may represent a promising therapeutic target to treat obesity, as this tissue has been shown to regulate energy expenditure through non-shivering thermogenesis. Three different strategies could be employed for therapeutic targeting of human thermogenic adipocytes: increasing BAT mass through stimulation of BAT progenitors, increasing BAT function through regulatory pathways, and increasing WAT browning through promotion of beige adipocyte formation. However, these strategies require deeper understanding of human brown and beige adipocytes. While murine studies have greatly increased our understanding of BAT, it is becoming clear that human BAT does not exactly resemble that of the mouse, highlighting the need for human in vitro models of brown adipocytes. Several different human brown adipocyte models will be discussed here, along with the potential to improve brown adipocyte culture through recreation of the BAT microenvironment.